The Effect Of Product Development, Price, And After-Sales Service On Purchase Intention Mediated By Electronic Word Of Mouth On Ryu Brand Power Tool Products In Jakarta, Indonesia - Djadja Nurdjaman; Ratlan Pardede (Al-Makki Publisher, 2024)
This study explores the impact of product development, pricing strategies, and after-sales service on purchase intention, with a specific focus on the mediating role of electronic word of mouth (eWOM) in the context of RYU brand power tool products in Jakarta, Indonesia. The research aims to identify how these key factors influence consumer behavior and decision-making processes in a competitive market environment. Data were collected through surveys from a sample of consumers in Jakarta, and the relationships between variables were analyzed using structural equation modeling (SEM). The findings reveal that product development and price significantly affect purchase intention, while after-sales service exerts a moderate influence. Moreover, eWOM is found to be a critical mediator that amplifies the impact of these factors on purchase intention. This study provides valuable insights for marketers and business practitioners in enhancing consumer engagement and driving sales through strategic focus on product innovation, competitive pricing, and effective after-sales services, while leveraging the power of eWOM.